Calorimetric and computational study of enthalpy of formation of diperoxide of cyclohexanone - Romero, Jorge Marcelo (2007)
A thermochemical rather simple experimental technique is applied to determine the enthalpy of formation of Diperoxide of ciclohexanone. The study is complemented with suitable theoretical calculations at the semiempirical and ab initio levels. A particular satisfactory agreement between both ways is found for the ab initio calculation at the 6-311G basis This set level. Some possible extensions of the present procedure are pointed out.